EFFECTS OF PARA-DICHLOROBENZENE AND SODIUM AZIDE ON GERMINATION AND SEEDLING GROWTH OF SESAME ( Sesamum indicum L.) (FUDMA JOURNAL OF SCIENCES, 2021)
ABSTRACTSesame is an important source of income and edible oil particularly in sub-saharan Africa. Its cultivation is constrains by many factors including lack of improved varietiess, pests and disease and abiotic stresses. Creating genetic variability could provide a base upon which improvement could made. This research was carried out to evaluate the effect of Sodium Azide and Para-dichlorobenzene on Germination and Seedlings growth of three sesame varieties (Ex-sudan, E-8 and JAN-IRI). Pot experiments were conducted during 2017 and 2018 seasons using completely randomized design (CRD). The treated seeds were planted and resulting plants (M0) were allowed to produce seeds. The seeds of the M0 were used in generating M1 plants which were used to evaluate the effect of the mutagens. Few days to germination were recorded in seeds treated with 3.0 mM So dium azide (3.0 days) or 3.0 mM Para-dichlorobenzene (3.0 days) in EX-SUDAN as well as seeds treated with 3.0 mM Sodium azide (3.0 days) in E-8. Percentage germination was significantly increased The highest shoot length was obtained when EX-SUDAN was treated with 2.0 mM (19.3cm) or 3.0 mM Sodium azide (18.2cm while highest root length was obtained when JAN-IRI and EX-SUDAN were treated with either 1.0 mM Para-dichlorobenzene (4.2cm) or 3.0 mM Sodium azide (3.8cm). The mutagens (Sodium azide and Para-dichlorobenzene) could be used to create variability for genetic improvement of Sesame.
Keywords: Sesame, Chemical Mutagens, Germination, Vegetative Characters, Genetic variability